High sensitivity variable-temperature infrared nanoscopy of conducting oxide interfaces - Weiwei Luo (Nature Portfolio, 2019)
Two-dimensional electron systems in oxide heterostructures have complex interactions that, once well understood, are expected to result in a powerful platform for electronic devices. Luo et al. show how near-field optical microscopy can perform high-resolution imaging of conducting regions in LaAlO3/SrTiO3 interfaces.